Kerangka Hukum Perjanjian Yang Efektif dan Aman Di Era Globalisasi Bisnis - Muslim Muslim; Pristika Handayani; Alwan Hadiyanto (Universitas Semarang, 2025)
This study aims to analyze the necessity of reforming contract law concepts to be more adaptive to the development of digital technology and personal data protection within the context of business globalization. The urgency of this research lies in the increasing use of information technology and artificial intelligence (AI) in modern business contracts, which introduces new legal challenges such as authentication, validity, and cross-jurisdictional data protection. This research employs a normative juridical method with a conceptual and comparative legal approach, examining both national legal instruments and international conventions. The findings reveal that Indonesia’s traditional contract law remains inadequate in accommodating electronic contracts, smart contracts, and personal data protection issues. The novelty of this research lies in the integration of legal certainty, good faith, contractual balance, and technology-based data protection principles into the proposed framework for international contract law. The study concludes that reforming contract law is urgent to enhance legal certainty and protect the parties involved in global contracts. It recommends establishing new legal norms in the Civil Code and sectoral regulations to recognize the validity of digital contracts, provide legal recognition for smart contracts, and harmonize personal data protection with international standards such as the GDPR and UNIDROIT Principles. Penelitian ini bertujuan menganalisis kebutuhan pembaruan konsep hukum perjanjian yang adaptif terhadap perkembangan teknologi digital dan perlindungan data pribadi dalam konteks globalisasi bisnis. Urgensi penelitian terletak pada meningkatnya penggunaan teknologi informasi dan kecerdasan buatan (AI) dalam kontrak bisnis modern yang memunculkan tantangan hukum baru, seperti otentikasi, keabsahan, dan perlindungan data lintas yurisdiksi. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan konseptual dan perbandingan hukum, mengkaji instrumen hukum nasional serta konvensi internasional. Hasil penelitian menunjukkan bahwa hukum perjanjian tradisional di Indonesia belum memadai dalam mengakomodasi kontrak elektronik, smart contracts, dan isu perlindungan data pribadi. Kebaruan penelitian ini terletak pada integrasi prinsip legal certainty, good faith, keseimbangan kontraktual, dan perlindungan data berbasis teknologi ke dalam kerangka hukum perjanjian internasional yang diusulkan. Kesimpulannya, pembaruan hukum perjanjian bersifat mendesak untuk meningkatkan kepastian hukum dan perlindungan para pihak dalam kontrak global. Penelitian ini merekomendasikan pembentukan norma baru dalam KUH Perdata dan peraturan sektoral yang mengatur keabsahan kontrak digital, pengakuan smart contracts, serta harmonisasi perlindungan data pribadi dengan standar internasional seperti GDPR dan UNIDROIT Principles.